Application of ERT and GPR geophysical testing to the subsoil characterization of cultural heritage sites in Napoli (Italy). (July 2017) - Evangelista, Lorenza; de Silva, Filomena; d'Onofrio, Anna; Di Fiore, Vincenzo; Silvestri, Francesco; Scotto di Santolo, Anna; Cavuoto, Giuseppe; Punzo, Michele; Tarallo, Daniela
Abstract: The paper describes two recent examples of application of Electrical Resistivity (ERT) and Ground Penetrating Radar (GPR), for reconstructing buried subsoil and structural geometries in two historical sites in the city of Napoli. Both investigation sites were characterized by complex environmental and logistic conditions. The first case study was an ancient hypogean cavity excavated in the tuff, where the integration between ERT and GPR allowed to identify the depth of the soft rock below the natural and anthropic filling. The second investigation was finalized to detect the foundation geometry of a high monumental bell tower resting on loose alluvial and pyroclastic soils. In both cases, the joint interpretation of ERT and GPR tests confirmed the preliminary knowledge on the subsoil and addressed further direct investigation aimed at the stability and safety of the historical sites.